Electrical contacting of High-Velocity-Air-Fuel sprayed NiCr20 coatings by brazing. Issue 1 (May 2021) - Bobzin, K; Wietheger, W; Heinemann, H; Liao, X; Vogels, C
Abstract: Thermally sprayed heater coatings can be used to control the surface temperature of parts and tools. A crucial point for such applications that has been neglected in the past is a reliable electrical contact with the power supply. One possible solution is the soldering or brazing of cables and cable connectors onto the heater coating. In this study, the possibility of brazing cable connectors to High-Velocity-Air-Fuel sprayed NiCr20 coatings was investigated to ensure electrical contact. The eutectic Ag-Cu filler was used for the vacuum brazing process. The insufficient wetting of the filler on the as-sprayed coating surface and the favored wetting of this filler on the copper cable connector led to low joint quality. This joint was improved by grinding the coating surface and changing the cable connector's material. Furthermore, measurements of the heater coatings' electrical resistance confirmed that electrical contacting by brazing is possible without significant influence on the heater coatings' properties.